Work value orientations and worker well-being in the new economy: Implications of the job demands-resources model among internet freelancers. Issue 9 (10th September 2018) - Shevchuk, Andrey; Strebkov, Denis; Davis, Shannon N.
Abstract : Purpose: The purpose of this paper is to integrate work values research with the Job Demands–Resources model to assess the role that work value orientations play in self-employed workers' subjective well-being. Design/methodology/approach: The paper analyzes unique data on freelancers participating in an online labor market ( n =9, 984). Findings: Intrinsic work values are associated with greater subjective well-being, whereas extrinsic work values are associated with lower subjective well-being. Consistent with the buffer hypothesis, intrinsic work value orientation reduces the negative effect of working hours on worker's well-being, and extrinsic orientation enhances the negative effect. Originality/value: This paper calls into question the importance of working conditions relative to worker values when assessing the role that job demands and resources play in the new economy. As work becomes more demanding and employment relations more flexible, personal resources such as work value orientations may become increasingly important for worker's well-being.